Lithium dancing (hidden in plain sight) - Ellis, Simon (The International Journal of Screendance, 2022)
In this article I explore screendance’s affair with social media, and the logics of production and consumption endemic to dancing for and with smartphones. I use an incidental encounter with two people making a dance video to try and make sense of the ways in which screendance practices and practitioners are being changed by social media technologies. The writing is built on the work of Harmony Bench, Shoshana Zuboff, Alan Jacobs, Zygmunt Bauman, Neil Postman, Yuk Hui and Annie Pfingst and Helen Poynor. I use their scholarship and art to construct an experimental and non-linear seven-part narrative about how screendance can become a set of practices that visibly contradict the extractive datafication of humans in motion. Part 1—Two young people and their camera—describes the encounter with two people filming their dancing, and serves as the platform on which this writing is based. In part 2—An assumption about what happened next—I introduce the theme of hiding that runs throughout the article, and make a case for my assumption that these two people were making their screendance for social media. Part 3—Algorithmic choreography—introduces the relationship between choreography in screendance and social media algorithms. Part 4—Being in (the) economic common—explores the digital commons as outlined by Bench, and its relationship to visibility, technology and profit-making. Part 5—Myth and the right to a future tense—discusses Jacobs and Zuboff and how they both deploy hiding to consider a future that transcends technocratic rationalism. In part 6—Hidden in the future I zip forward far into the future and remember a 2016 screendance work by Annie Pfingst and Helen Poynor. I do this to as a strategy to imagine a non-technocratic world. Finally, part 7—To distill production from consumption—describes how, through social media, we in screendance have acquired a logic of consumption disguised or hidden as a mode of production.